Analysis of The Compliance of The 2025 Fiscal Year APBKal Draft with Ministry of Home Affairs Regulation No. 20 of 2018 and Bantul Regent Regulation No. 52 of 2024: A Case Study of Bangunjiwo Village, Bantul - Soraya Dewi Wisnu Putri; Luthfi Ihsanti Hamidah; Mutiara Indah Pratiwi; Maslakhatul Mufidah Muniroh (Devotion : Journal of Research and Community Service, 2026)
This study analyzes the compliance of the 2025 Fiscal Year Village Revenue and Expenditure Budget (APBKal) of Bangunjiwo Village, Kapanewon Kasihan, Bantul Regency, Yogyakarta, with the provisions of Minister of Home Affairs Regulation No. 20 of 2018 and Bantul Regent Regulation No. 52 of 2024. Employing a qualitative descriptive approach, data were collected through documentation review, semi-structured interviews with village planning officials, and examination of publicly available budget information on the official village website. The study evaluates nine key stages of the APBKal preparation process, covering planning hierarchy, public consultation, Bamuskal approval, evaluation by Kapanewon, budget determination, administrative use of technology, publication and transparency, and special provisions for Village Fund allocation. The findings indicate that Bangunjiwo Village demonstrates a generally high level of regulatory compliance. The planning process adhered to the hierarchical sequence from RPJMKal to RKPKal and APBKal, coordinated systematically by the Village Secretary. Public consultations meaningfully involved community leaders and village institutions, reflecting substantive participation rather than mere procedural formality. Budget administration was conducted through the Siskeudes and E-RAB applications, ensuring administrative orderliness. Village Fund allocations for food security (20.21%) and Direct Cash Assistance (11%) met the prescribed thresholds. Budget information was transparently published through the official village website in accordance with applicable regulations. However, one notable non-compliance was identified: the Bamuskal approval of the draft APBKal was conducted in December 2024, exceeding the deadline of November as stipulated by Bantul Regent Regulation No. 52 of 2024.